Keefektifan Model Pembelajaran Kooperatif Tipe TGT (Team Games Tournament) pada Pokok Bahasan Pecahan Sederhana Kelas III SDN Tanjungsari 1 Sidoarjo - RAHMADANI, APRIANTI (Trapsila: Jurnal Pendidikan Dasar, 2019)
In elementary school learning is a time of planting a foundation to build fundamental concepts that will later be developed for the next learning material. Effective and fun learning can help students to understand concepts in mathematics, one of which is simple fraction operations. Simple fractions are included that are difficult for some students to understand. This can be seen from the number of students who sit at the high level of elementary school some have not mastered the subject of this simple fraction, so that they have many difficulties in learning higher mathematical topics. Through effective learning models and teacher guidance is expected to help students learn simple fractions. This study aims to show the effectiveness of the TGT (Team Games Tournament) cooperative learning model on the subject of simple fractions class III SDN Tanjungsari I Sidoarjo. Indicators of learning effectiveness include four aspects, namely mastery learning outcomes, teacher activities, student activities, and student responses. Data collection used in this study is a test method for completeness of learning outcomes, teacher activity observation methods, student activity observation methods, and student questionnaire methods for student responses. The results of this study (1) The completeness of student learning outcomes in class III of SDN Tanjungsari I Sidoarjo is said to be complete with a percentage of 82.60% (2) The percentage of teacher activity is included in the high category with a percentage value of 81.6% (3) The percentage of class student activities III SDN Tanjungsari I Sidoarjo included in the category of active student activities with a percentage value of 85.4% (4) The response of students in class III SDN Tanjungsari I Sidoarjo was positive with a percentage of 60% providing strong support and 40% providing very strong support. So that the TGT (Team Games Tournament) type of cooperative learning model on the subject of simple class III fractions at SDN Tanjungsari 1 Sidoarjotakes place effectively.